2015
DOI: 10.1149/06801.1597ecst
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protective Coatings for SOFC Interconnects

Abstract: Chromium poisoning is a widely recognized degradation process in solid oxide fuel cells (SOFC). Stainless steel interconnect plates, in direct contact with the cathode, have been identified as the major chromium source, raising a need for electrically conducting protective coatings for the interconnects. This work evaluates four different manganese-cobalt protective coatings manufactured on thin steel foils, made by three commercial companies and a research centre. Area specific resistance, coating microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…For the oxygen side, (Co,Mn) 3 O 4 spinel coatings have been shown to be good candidates with various deposition methods and compositional variations having been tested [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Ce/Co coatings, deposited as a metallic layer and oxidized to a spinel during operation in the stack, have also showed promising chromium retention and oxidation protection properties [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…For the oxygen side, (Co,Mn) 3 O 4 spinel coatings have been shown to be good candidates with various deposition methods and compositional variations having been tested [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Ce/Co coatings, deposited as a metallic layer and oxidized to a spinel during operation in the stack, have also showed promising chromium retention and oxidation protection properties [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…13. Briefly, the testing system consists of a multisample stack with the samples electrically connected in series and arranged to form a sandwich structure.…”
Section: Methodsmentioning
confidence: 99%
“…15 Besides, the method has been previously validated with a commercial Ce/Co coated Sandvik Sanergy HT steel used as benchmark: 13 a very low contact cell unit resistance (ca. 5 m cm −2 ) has been measured at 700…”
Section: Methodsmentioning
confidence: 99%
“…It was later demonstrated that it prevents Cr diffusion to the top layer [11]. Several studies confirmed the beneficial effects of Ce [29] [30], even in the case of discrete particles rather than as a Ce-layer [31]. Ce was also shown to act as diffusion barrier against iron diffusion from the steel [22].…”
Section: Introductionmentioning
confidence: 94%